2021
DOI: 10.2147/cmar.s295646
|View full text |Cite
|
Sign up to set email alerts
|

Change in Maximal Esophageal Wall Thickness Provides Prediction of Survival and Recurrence in Patients with Esophageal Squamous Cell Carcinoma After Neoadjuvant Chemoradiotherapy and Surgery

Abstract: This study aimed to evaluate the relationship of the percentage decrease of maximal esophageal wall thickness with pathological complete response (pCR) and recurrence in esophageal squamous cell carcinoma (ESCC). Patients and Methods: A total of 146 ESCC patients treated with neoadjuvant chemoradiotherapy (NCRT) and surgery were included. The prognostic factors for overall survival (OS) and disease-free survival (DFS) were analyzed. The recurrence site, time, and frequency were included in the analysis. The pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“… 28 The other variables (SII, SIRI and PNI) were calculated by the following formula: PNI = ALB (g/L) +5 × LY (10 9 /L), SII = PLT × NEUT/LY and SIRI = MONO × NEUT/LY. 17 , 18 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 The other variables (SII, SIRI and PNI) were calculated by the following formula: PNI = ALB (g/L) +5 × LY (10 9 /L), SII = PLT × NEUT/LY and SIRI = MONO × NEUT/LY. 17 , 18 …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, more and more integrative hematological indicators, including systemic inflammation response index (SIRI), systemic immune-inflammation index (SII) and prognostic nutritional index (PNI), were also applied for pCR prediction after nCRT in several cancers. 17 , 18 …”
Section: Introductionmentioning
confidence: 99%
“…Although some tumor cells were killed after radiotherapy, there was little change in the maximum tube wall thickness ( 22 24 ). Wu's team found that in patients with esophageal cancer undergoing radiotherapy and chemotherapy, the percentage of maximum wall thickness reduction was independently associated with pathological complete response ( p = 0.027), and could predict the recurrence of the disease ( 25 ). Wongwaiyut's team found that the survival of patients with esophageal cancer with a maximum wall thickness of <10 mm and ≥10 mm was different, and the larger the maximum wall thickness, the worse the prognosis of patients ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accurate prediction of the pCR before surgery is crucial for the decision of whether to continue observation or radical surgery in the observation period after nCRT. A single-center retrospective study ( 63 ) with 146 ESCC patients treated with nCRT concluded that a ≤40% reduction in the maximal esophageal wall thickness following nCRT was strongly related to low pCR rate, short survival time, and high risk of recurrence. However, the prediction of the efficacy of nCRT-based CT alone is insufficient.…”
Section: The Strategies To Accurately Predict the Efficacy Of Neoadju...mentioning
confidence: 99%